An analysis of overweight and obesity in South Africa: the case of women of childbearing age - Nglazi, Mweete Debra (Department of Public Health and Family Medicine, 2022)
This thesis used nationally representative data from the 2008 - 2017 National Income Dynamics Study, 1998 and 2016 South African Demographic and Health Surveys and 2005/06 and 2010/11 Income and Expenditure Surveys to examine prevalence, socioeconomic inequality, and determinants of overweight and obesity among non-pregnant women of childbearing age (15 to 49 years) (WCBA) in South Africa over time. It also assessed socioeconomic inequality in the intergenerational transmission of overweight and obesity from mothers to their offsprings among 10,735 mother-offspring pairs and decomposed socioeconomic inequality in household ultra-processed food (UPF) product spending in samples of 16,209 households in 2005/06 and 17,217 households in 2010/11. Overweight and obesity in WCBA in South Africa increased between 1998 and 2017 with factors including increased age, self-identifying with the Black African population group, higher educational attainment, residing in an urban area, and wealth contributing to the rise. Smoking had a protective effect on being overweight and obese. Overweight and obesity were also increasingly prevalent among wealthier than poorer WCBA in South Africa between 1998 and 2016. It was found that UPF expenditure increased between 2005/6 and 2010/11, accounting for a substantial share of poorer households' expenditures than their wealthier counterparts over time. Although factors explaining socioeconomic inequality in the intergenerational transmission of overweight and obesity differed by offspring sex, intergenerational overweight and obesity occur more frequently among wealthier mother-offspring pairs than their poorer counterparts. Key factors explaining inequalities in intergenerational overweight and obesity include the mother's socioeconomic status, education and exercise habits. This study improves the empirical understanding of the burgeoning overweight and obesity challenges among women, especially in South Africa, who are likely to transmit them to their offspring. Policy to address these issues should not only be about health services but also focus on the social determinants of health inequalities.